2023
DOI: 10.1186/s12964-023-01151-y
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic and therapeutic value and clinical implications of fibroblast activation protein-α as a novel biomarker in colorectal cancer

Abstract: The identification of contributing factors leading to the development of Colorectal Cancer (CRC), as the third fatal malignancy, is crucial. Today, the tumor microenvironment has been shown to play a key role in CRC progression. Fibroblast-Activation Protein-α (FAP) is a type II transmembrane cell surface proteinase expressed on the surface of cancer-associated fibroblasts in tumor stroma. As an enzyme, FAP has di- and endoprolylpeptidase, endoprotease, and gelatinase/collagenase activities in the Tumor Microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 145 publications
0
4
0
1
Order By: Relevance
“…FAP is heavily involved in tissue remodeling and promotes tumorigenesis through multiple mechanisms, including angiogenesis, with the promotion of surrounding tissue invasion, immune suppression, epithelial–mesenchymal transition, drug resistance, and stem cell promotion [ 27 ]. It has also been shown that FAP overexpression is associated with lymphocyte-dependent immune responses [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…FAP is heavily involved in tissue remodeling and promotes tumorigenesis through multiple mechanisms, including angiogenesis, with the promotion of surrounding tissue invasion, immune suppression, epithelial–mesenchymal transition, drug resistance, and stem cell promotion [ 27 ]. It has also been shown that FAP overexpression is associated with lymphocyte-dependent immune responses [ 28 ].…”
Section: Resultsmentioning
confidence: 99%
“…As such, the biomarker could be a useful tool in other diseases, as FAP has been shown to be upregulated and influential in multiple types of cancer as well as non-cancerous diseases including acute coronary syndrome, fibrosis, and arthritis [ 54 , 55 , 56 , 57 ]. For future studies, it would be interesting to investigate if C3F could show other biomarker properties like those of FAP protein quantification as multiple studies have shown an indication of its prognostic or predictive potential in multiple cancer types including renal, colorectal, hepatic, and lung cancer [ 25 , 58 , 59 , 60 ]. It is also of great interest to investigate the value of C3F as a predictive or pharmacodynamic biomarker for various FAP-targeting treatment procedures as this could be where the use of C3F will be applied in the future.…”
Section: Discussionmentioning
confidence: 99%
“…As suggested earlier, exploiting the possible combination of CD31 (to specify endothelial cells) with CD34 and VAP-1 (as shared endothelial/ mesenchymal markers) for cell sorting may also provide further data on the altered production of NKX2-3 between normal and CRC or polyp samples from humans. It is yet unknown whether various CRCassociated mutations (KRAS, NRAS, and BRAF) 39 or fibroblast activation protein (FAP) production 40 may modify or correlate with the expression of NKX2-3. In addition, follow-up studies of samples taken from various stages of cancer progression and therapeutic response and larger cohort may further pinpoint differential representation of the FAP-positive CAF compartment with various degrees of NKX2-3 expression.…”
Section: Discussionmentioning
confidence: 99%